Study on fungal contaminants in aborted calves of cattle herds in Iran - Samaneh Eidi; Hesam A. Seifi; Soheil Sadr; Hamideh Zeinali (Veterinary Medicine and Science)
Abstract Background/Objective Abortions in livestock herds are a major contributor to economic losses. The incidence of fungal aetiology has been reported thus far. The purpose of this study is to investigate the prevalence of abortions due to fungi in referred cases to the Center of Excellence in Ruminant Abortion and Neonatal Mortality, Veterinary Hospital of Ferdowsi University of Mashhad, Mashhad, Iran, from different provinces of Iran. Methods A total of 200 calves were referred between 2018 and 2022. Samples were taken from the lungs, liver, spleen and abomasum. The fungi present in the cultures were analysed microscopically and morphologically. Results There were varying contamination levels in the liver, spleen and lungs, with prevalence ranging from 15% to 17%. Abdomasum had a 1% prevalence rate. Different fungal species, including Cryptococcus neoformans (C. neoformans), Aspergillus spp., Rhodotorula spp., Trichosporon spp., Candida spp., Geotrichum spp., Penicillium spp. and Mucor spp., were identified, indicating a diverse range of pathogens affecting calves. The specificity of fungal contaminants in certain organs, such as C. neoformans, Rhodotorula spp. and Trichosporon spp., highlighted the organ's microenvironment as a potential factor influencing fungal growth. Conclusion As fungi are emerging as a significant cause of morbidity and mortality in animals, the growing role of fungi in livestock abortions should be investigated. As clinical signs are not pathognomonic, laboratory help is imperative to confirm fungal abortion diagnosis.